First record of the genus Dolichomitus Smith (Hymenoptera: Ichneumonidae: Pimplinae) from Vietnam, with description of one new species - Pham, Nhi Thi; Broad, Gavin R.; Zwakhals, Kees (Zootaxa, 2012)
The genus Dolichomitus Smith, 1877 is recorded from Vietnam for the first time with description of a new species, D. lami sp. nov., from Hoang Lien National Park, Lao Cai Province. Besides, D. melanomerus (Vollenhoven) is recorded as new for the country from specimens collected in Tam Dao National Park, Vinh Phuc Province and Hang Kia-Pa Co Nature Reserve, Hoa Binh Province.